PERHITUNGAN DAN PEMOTONGAN PPH PASAL 23 PADA DINAS PEMBERDAYAAN MASYARAKAT, DESA, KEPENDUDUKAN DAN PENCATATAN SIPIL PROVINSI JAWA TENGAH TAHUN 2019 - Azalia Irza Ramawardhani; Resi Yudhaningsih (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2020)
Article 23 Income Tax is a tax withheld on income that received or accrued by a domestic taxpayer (individual or entity) and permanent establishment coming from the capital, the delivery of services, or carrying out activities other than those that already withheld under Article 21 Income Tax. This final project aims to find out the suitability of calculation and withholding of Article 23 Income Tax at Department of Community Empowerment, Village, Citizenship and Civil Registration of Central Java Province according to Law No 36 of 2008 concerning Income Tax. Data collection methods used in this final project are interview method and documentation study, while in writing forms use description and exposition. Based on the calculations that have been done, there are differences in the calculation and withholding of Article 23 Income Tax between Department of Community Empowerment, Village, Citizenship and Civil Registration of Central Java Province and Law No 36 of 2008. The difference in calculation is due to miscalculation and error in determining rates between partners with Tax Identification Number (TIN) and partners without TIN.